Peningkatan kemampuan representasi matematik peserta didik dengan menggunakan model problem based learning (PBL) berbantuan media software Geogebra - Setio Priyono; Redi Hermanto (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2015)
This research aims to know the improvement of students’s mathematical representastion skill Bette beetwen using PBL Model helped geogebra software media and using PBL model without helped geogebra software media.The method is experiment method. The population were all of the tenth grade mathematic and nature students of  Senior High School 1 Tasikmalaya using 2013 Curiculum with scientific approach. The sample of this research was randomly selected, two classes of the population, X MIA 4 as experiment class and X MIA 5 as control class. The result of this research is (1) the improvement of the students’s mathematical representation skill using PBL model helped by geogebra software media is not better than or equal with those using PBL model without helped by geogebra software media; and (2) the students’ motivation of study during following lesson using PBL model helped geogebra software media were in medium criteria.